Meanings of multiethnicity : a case-study of ethnicity and ethnic relations in Singapore - Lai, Ah Eng. 4 0 16; 5 (Kuala Lumpur ;;New York : Oxford University Press, 1995)
This book explores the various meanings of multiethnicity in Singapore. By focusing on selected arenas and processes, it examines how 'ethnic' and 'interethnic' dimensions interact in the construction of community and identity in the context of nation-building. Its analysis ranges from detailed ethnography to discussion of broad features and issues, and links micro and macro data by juxtaposing the two levels and showing how they interact. Emphasis is placed on the local, specifically the residential community, it being a basic component in nation-building and a mediator of national identity. Theoretically, the study addresses several issues involving ethnic identity and community, modes of ethnic interaction, and nation-building in a multiethnic context. It confirms and elaborates on the symbolic-affective power of ethnicity, the contradictory trends of ethnic harmony and tension in interaction, and the structuring impact of macro forces, in particular majority-minority group responses and the state's role, in the arenas of culture and economy. Empirically, it documents the Singapore case of how individuals, groups, and the state manage ethnicity and ethnic relations for viable multiethnic living.
Includes bibliographical references (p. [206]-222) and index.
Keywords: 2 -- 0; 6; Ethnicity -- Singapore. -- 20; Ethnic relations. -- Singapore -- 20; 2